Human Resource Management Strategy in an Effort to Improve the Quality of Umroh Services at Travel Sutra Sidoarjo - Dandy Dimas Pranata; Acep Samsudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Human Resources is a strategic element that plays a key role in determining the success and sustainability of an organization. One of the companies that prioritizes service is the Umrah travel company. The quality of human resources greatly determines how a travel company is able to provide maximum service to customers. This study aims to determine the human resource management strategy in improving the quality of its service to customers of Travel Sutra Sidoarjo. This study uses a qualitative method formulated using SWOT analysis and data collection techniques through interviews, observations, documentation, and triangulation. The object of research in this study is Travel Sutra Sidoarjo, involving directors, employees, and customers as informants. The results of this study, based on the SWOT matrix analysis, obtained IFAS results showing strengths with a score of 2.17 and weaknesses with a score of 0.89. The EFAS results show opportunities with a score of 2.19 and threats with a score of 0.86. Based on the SWOT Analysis Diagram, Travel Sutra Sidoarjo shows Quadrant 1 using an aggressive strategy, namely the company has opportunities and strengths, so that it can take advantage of existing opportunities in improving the quality of travel services.